Kepemimpinan Kepala Sekolah Dalam Peningkatan Kinerja Profesional Guru (Studi Pada Sdit As Saman Kecamatan Jati Agung Kabupaten Lampung Selatan) - Fitri Dwi Rahmawati; Adhy Firdaus; Joned Ceilendra Saksana (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2024)
This study uses a descriptive qualitative approach. Data collection is carried out by means of observation, interviews and documentation. The data analysis techniques used are triangulation of data collection methods and triangulation of places. This study discusses the leadership of the head of SDIT ASSAMAN in improving teacher professional performance. The problem that occurs is that teachers as the driving force of education still do not master technology so that learning is often hampered and lagging behind other schools. This research involved 5 resource persons consisting of principals, teachers and staff. The results of the study show that teachers who do not master technological developments are not the only factor inhibiting education in school institutions. Because, what is the driving factor for improving the quality of education is the cooperation between principals, teachers, staff and guardians. All elements in the institution are integrated in realizing the school's mission and mission. The principal routinely supervises and coordinates so that teaching and learning activities run effectively